2013
DOI: 10.1007/s00192-013-2109-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly purified collagen coating enhances tissue adherence and integration properties of monofilament polypropylene meshes

Abstract: Polypropylene mesh coated with purified collagen gel increases adherence to tissue, promotes a less intense and lasting inflammatory response and triggers a greater organization and packing arrangement of collagen fibers in the late phase of implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Patients with recurrent urinary incontinence have worse outcomes and a higher likelihood of failure in any subsequent anti-incontinence technique, mostly in the long term, and fibrotic tissue around urethra can limit its mobility and prevent sling to achieve ideal support to the urethra [16][17][18][19][20][21]. Although SIMS is a very heterogeneous group, worse long-term results among patients with previous surgeries support the hypothesis that longstanding success could depend on the grade and pattern of interaction between the sling and suburethral support tissues [22].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with recurrent urinary incontinence have worse outcomes and a higher likelihood of failure in any subsequent anti-incontinence technique, mostly in the long term, and fibrotic tissue around urethra can limit its mobility and prevent sling to achieve ideal support to the urethra [16][17][18][19][20][21]. Although SIMS is a very heterogeneous group, worse long-term results among patients with previous surgeries support the hypothesis that longstanding success could depend on the grade and pattern of interaction between the sling and suburethral support tissues [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques like coating with highly purified collagen or fetal collagen both in a rat model [44,45] and platelet-enriched plasma in a rabbit model [46] have shown promising biocompatibility improvements in vivo. Even a study using a macaques model for the investigation of extracellular matrix regenerative graft reported that regenerative extracellular matrix graft attenuated the negative impact of polypropylene on the vagina [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this study, several others, albeit using different methods, have described histological and molecular changes after the implantation of biomaterials, in particular, polypropylene ( 8 , 9 , 10 , 11 ). An inflammatory response to macroporous monofilament PP was demonstrated in explanted meshes from humans one year after implantation and it was observed that this material had little long-term influence on the extracellular matrix composition, represented by the fraction of collagen and elastin in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the biological response is not only a consequence of the contact between host and polymer, but is also a result of chemical changes in the preparation process ( 7 ). Several mechanical and histological characteristics secondary to PP implants in living organisms have been demonstrated ( 8 - 10 ). Most of the histological and immunohistochemical evaluations are based on the description of cellular types and/or semi-quantitative measurements of their distribution in randomized samples ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%